Thymic gland aspects in childhood: morpho-functional reciprocal relationships betwen thymus, nervous and endocrine system, in particular, with the somatotrophic axis hormones - N. N. Minyailova; Yu. I. Rovda; A. V. Vedernikova; A. V. Shabaldin; S. F. Zinchuk; O. V. Shmakova; A. V. Golomidov; A. A. Lobykina; V. V. Sokharev (Медицинская иммунология, 2023)
Thymic gland (thymus) represents a huge mystery for biology, medicine (primarily immunology), including pediatric issues. Complexity of the study is determined by the multiplicity of integral connections of thymus with other components of immune system, neuroendocrine, hematopoietic systems, connective tissue, different organs and cells which provide appropriate barrier function. Discerning the direct thymic function from this continuum, or determining specific role of molecular factors (neuropeptides, growth hormone, etc.) upon the immune physiology represents a problem which is not yet resolved. In this review article dedicated to the current state of the problem, we consider the morphological and functional relationships between thymus, neuroendocrine system and, in particular, with hormones of the somatotropic axis. These interactions may also manifest by clinical heterogeneity which may be associated with impaired morphogenesis (organogenesis) at a very early stage of embryogenesis; namely, under the influence of gene family that determine the fate of each segment of the embryo-Hox genes which control the expression of other, functionally interconnected genes. Previously, T lymphocytes produced by the thymus and brain neurons have been shown to express the same antigen (Thy antigen), which was considered a specific antigen of T lymphocytes. A common molecular language, mediated by the molecules of intercellular interaction, was revealed which is used for the signal exchange between the cells, tissues and organs regulating the three mentioned systems (nervous, endocrine and immune). The interest of pediatricians in this field is associated with definite concept of human ontogenesis, from birth to elderly age, with thymic gland playing the main role, since antenatal period to early childhood. The main line of reasoning in this research area is not only theoretical, but also important from practical point of view. Since any critical involution of the thymus is accompanied by reduced number of produced and exported cells, a hormone-based therapy may be an alternative strategy to restore the organ by increasing thymocyte proliferation, and exporting mature T cells to peripheral lymphoid organs. Great opportunities have been opened in clinical immunology due to development of effective epistemological methods, e.g., genetic knock-out, transgenic animal models with human stem cell transfer, transplantation of hematopoietic and immunopoietic cells in primary and secondary immunodeficiencies, immune cell malignancies, autoinflammatory diseases, and, finally, infections of the immune system.